2019
DOI: 10.1038/s41598-019-44934-5
|View full text |Cite|
|
Sign up to set email alerts
|

Regulation of the Hepatitis B virus replication and gene expression by the multi-functional protein TARDBP

Abstract: Hepatitis B virus (HBV) infects the liver and is a key risk factor for hepatocellular carcinoma. Identification of host factors that support viral replication is important to understand mechanisms of viral replication and to develop new therapeutic strategies. We identified TARDBP as a host factor that regulates HBV. Silencing or knocking out the protein in HBV infected cells severely impaired the production of viral replicative intermediates, mRNAs, proteins, and virions, whereas ectopic expression of TARDBP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 61 publications
(75 reference statements)
0
13
0
Order By: Relevance
“…HBc is mostly known as the building block of the HBV capsid (Summers et al, 1975) but in recent years it has been shown that its function is not limited to this and also plays a role in cccDNA stability, transcription and epigenetic regulation (Newbold et al, 1995;Bock et al, 2001;Zlotnick et al, 2015;Chong et al, 2017), evasion of antiviral mechanisms (Lucifora et al, 2014), reverse transcription (Tan et al, 2015), cellular trafficking (Schmitz et al, 2010;Yang et al, 2014), genomic replication (Lott et al, 2000), and viral egress (Bardens et al, 2011). The field is also discovering more and more that HBc expression is extensively regulated by core promotor regulation, core mRNA modulation and post-translational modifications which highlights its importance in the life cycle (Buckwold et al, 1997;Sohn et al, 2006;Kohno et al, 2014;Qian et al, 2015;He et al, 2016;Bartusch et al, 2017;Lubyova et al, 2017;Heger-Stevic et al, 2018;Makokha et al, 2019). Initially, the impact on the capsid made HBc an appealing drug-target (Berke et al, 2017).…”
Section: The Hbc Interactomementioning
confidence: 99%
“…HBc is mostly known as the building block of the HBV capsid (Summers et al, 1975) but in recent years it has been shown that its function is not limited to this and also plays a role in cccDNA stability, transcription and epigenetic regulation (Newbold et al, 1995;Bock et al, 2001;Zlotnick et al, 2015;Chong et al, 2017), evasion of antiviral mechanisms (Lucifora et al, 2014), reverse transcription (Tan et al, 2015), cellular trafficking (Schmitz et al, 2010;Yang et al, 2014), genomic replication (Lott et al, 2000), and viral egress (Bardens et al, 2011). The field is also discovering more and more that HBc expression is extensively regulated by core promotor regulation, core mRNA modulation and post-translational modifications which highlights its importance in the life cycle (Buckwold et al, 1997;Sohn et al, 2006;Kohno et al, 2014;Qian et al, 2015;He et al, 2016;Bartusch et al, 2017;Lubyova et al, 2017;Heger-Stevic et al, 2018;Makokha et al, 2019). Initially, the impact on the capsid made HBc an appealing drug-target (Berke et al, 2017).…”
Section: The Hbc Interactomementioning
confidence: 99%
“…Interestingly, several RBPs previously identified as important for HBV replication were shown to participate in the control of HBV transcription and/or in RNA stability. This is the case in particular for the splicing factors HNRNPC, HNRNPK, PUF60, RBM24 and TARBP [75][76][77][78][79]. It is therefore conceivable that SRSF10 may associate with HBV nascent RNA in the nucleus to control its synthesis/elongation and/or its stability.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…The PXB-cell system was introduced as a highly reproducible model for HBV infection [7]; however, inoculum preparation from culture supernatants had been limited to the cell lines of genotype D [31][32][33]. Since the major genotype in the Asia-Pacific region is genotype C [34], the inoculum in this study was prepared from culture supernatant of T23, a genotype C-producing cell line [17,35]. While a significant increase in cccDNA level was reported around 40 days post-infection in HepG2-NTCP-K7 cells [36], cccDNA levels in PXB-cells 35 days after infection were not different between NA-treated and control groups (Fig.…”
Section: Discussionmentioning
confidence: 99%